Strikes, employee workplace representation, unionism, and trust: evidence from cross-country data - Addison, John T.; Teixeira, Paulino (Bonn, 2017)
"This paper investigates the determinants of industrial conflict in companies, using a multi-country workplace inquiry for 2009 and 2013 and various measures of strike activity. The principal goal is to address the effect of formal workplace representation on strikes, distinguishing in the first instance between works councils on the one hand and broadly equivalent trade union based entities on the other. The role of unionism is also central to this inquiry, not only with respect to the degree to which workplace representation is union dominated but also and more familiarly perhaps through workplace union density and the level at which collective bargaining is conducted. Attention is also paid to the quality of industrial relations, as reflected in dissonance, namely divergent assessments of managers and employee workplace representatives as to the state of industrial relations. Although country effects do matter, it is reported that works councils are associated with reduced strike activity. However, any such effect is sensitive in particular to the union status of work councilors and time. There is also some indication that collective bargaining at levels higher than the company can exacerbate strike activity but this effect does not persist, possibly because of decentralization and the development of hybrid bargaining structures. For its part, good industrial relations appears key to strike reduction, independent of workplace representation."